Investigating motivational dimensions for e-learning (VLE): a case study of UniKL BMI students / Annie Noorsafawati Abdul Sani - Abdul Sani, Annie Noorsafawati (2017)
Information Communication and Technology (ICT) has become important in education environment that improves the teaching and learning environment such as by using e- Learning. In Universiti Kuala Lumpur British Malaysian Institute (UniKL BMI) the e- Learning has been developed on the year 2010. The UniKL e-Learning also known as Learning Management System (LMS) was managed by each campus. The e-Learning website has contained the information such as subject, lecturer profile, student profile and sharing the learning material. This research has been conducted to evaluate e-Learning (VLE) using Website Evaluation Instrument (WebCHECK Professional), to investigate motivational dimensions which are Simulating, Meaningful, Organized and Easy to use between UniKL BMI students while using e-Learning (VLE) and to propose recommendation for developer to improve the motivational element in e-Learning (VLE). A total of 320 UniKL BMI students took part in answering a set of questionnaire related to e-Learning (VLE). The data from the surveys were analysed using Website Evaluation Instrument (WebCHECK Professional). The evaluation of e-Learning (VLE) using WebCHECK Professional shows that e-Learning (VLE) website is Awesome. The motivational dimensions of e-Learning (VLE) have shown the website is easy to use with a total score of 19.82. It is recommended that the developer should improve the design and user interface of the e-Learning (VLE) website.